Sensitivity of 3D gradient recalled echo susceptibility-weighted imaging technique compared to computed tomography angiography for detection of middle cerebral artery thrombus in acute stroke - Amit Agarwal; Kanupriya Vijay; Krishnamoorthy Thamburaj; Sangam Kanekar; Paul Kalapos (MDPI AG, 2014)
We aimed at comparing the sensitivity of magnetic resonance (MR) susceptibility-weighted imaging (SWI) with computed tomography angiography (CTA) in the detection of middle cerebral artery (MCA) thrombus in acute stroke. Seventy-nine patients with acute MCA stroke was selected using our search engine software; only the ones showing restricted diffusion in the MCA territory on diffusion-weighted images were included. We finally selected 35 patients who had done both MRI (including SWI) and CTA. Twenty random subjects with completely normal MRI (including SWI) exam were selected as control. Two neuroradiologists (blinded to the presence or absence of stroke) reviewed the SW images and then compared the findings with CT angiogram (in patients with stroke). The number of MCA segments showing thrombus in each patient was tabulated to estimate the thrombus burden. Thrombus was detected on SWI in one or more MCA segments in 30 out of 35 patients, on the first review. Of the 30, SWI showed thrombus in more than one MCA segments in 7 patients. CTA depicted branch occlusion in 31 cases. Thrombus was seen on both SWI and CTA in 28 patients. Thrombus was noted in two patients on SWI only, with no corresponding abnormality seen on CTA. Two patients with acute MCA showed no vascular occlusion or thrombus on either CTA or SWI. Only two case of false-positive thrombus was reported in normal control subjects. Susceptibility-weighted images had sensitivity and specificity of 86% and 90% respectively, with positive predictive value 94%. Sensitivity was 86% for SWI, compared with 89% for CTA, and this difference was statistically insignificant (P>0.05). Of all the positive cases on CTA (31) corresponding thrombus was seen on SWI in 90% of subjects (28 of 31). Susceptibility-weighted imaging has high sensitivity for detection of thrombus in acute MCA stroke. Moreover, SWI is a powerful technique for estimation of thrombus burden, which can be challenging on CTA.